Теоретико-методичні аспекти управління запасами - Колісник, Олена Пилипівна; Мазурок, Олена Павлівна (Державний податковий університет, 2023)
В статті розглянуто теоретико-методичні аспекти управління запасами. Предметом дослідження є теоретичні основи управління виробничими запасами підприємства. Метою статті є розкриття сутності поняття «запаси», їх класифікацію та види; розгляд методології аналізу запасів на підприємстві, аналіз теоретичних та емпіричних джерел. Для досягнення мети у статті узагальнено трактування сутності поняття «запаси» науковцями, національними та міжнародними положеннями. Наведено основні класифікаційні види запасів, розглянуто системи ефективного управління запасами у виробничій логістиці на основі концепції «Justintime» та традиційного підходу до управління запасами. Наведено основні методи та напрямки аналізу запасів. Проведення аналізу запасів підприємства можливе за допомогою різних методів: емпіричних, теоретичних, статистичних, методу економетричного, горизонтального та вертикального аналізу та ін.

Theoretical and methodological aspects of inventory management are considered in the article, because, in modern conditions, in connection with the need to quickly obtain reliable information, the problems of inventory accounting become especially relevant. The subject of the study is the theoretical basis of the management of production stocks of the enterprise. The purpose of the article is to reveal the essence of the concept of "inventory", their classification and types; consideration of the methodology of inventory analysis at the enterprise, analysis of theoretical and empirical sources with the help of theoretical and methodological methods. The main classification features that can be distinguished when dividing inventory are: purpose, location, time of storage at the enterprise, period of use, purpose of formation, form of ownership, structure. To achieve the goal, the article summarizes the interpretation of the essence of the concept of "inventory" by scientists, national and international regulations. The main classification types of stocks are presented, the systems of effective stock management in production logistics based on the "Justintime" concept and the traditional approach to stock management are considered. The "Justintime" method occupies an important place among them, and aims to produce and ship products at the exact time of their further use. And the traditional approach, on the contrary, assumes the availability of products in stock "just in case" to meet unpredictable demand. The main methods and directions of stock analysis are given. Analyzing the company's stocks is possible using various methods: empirical, theoretical, statistical, econometric methods, horizontal and vertical analysis, etc. These methods will help determine the influence of factors on the volume of inventory, develop a forecast for future years, which can positively affect the company's activities. Streamlining of primary documentation, improvement of operational and warehouse accounting of inventory, rationalization of document forms, improvement of the level of automation of accounting and settlement work contribute to better implementation of inventory accounting and analysis. But it is necessary to remember that for a reliable and accurate analysis, you need data for at least 10 years, which will help reduce the possible error to a minimum.
Theoretical and methodological aspects of inventory management
Keywords: запаси; активи; класифікація запасів; матеріальні запаси; методи аналізу запасів; управління запасами; іnventory; assets; inventory classification; material inventory; inventory analysis methods; inventory management